2019
DOI: 10.1111/1471-0528.15516
|View full text |Cite
|
Sign up to set email alerts
|

External validation and clinical usefulness of first‐trimester prediction models for small‐ and large‐for‐gestational‐age infants: a prospective cohort study

Abstract: Objective To assess the external validity of all published first‐trimester prediction models based on routinely collected maternal predictors for the risk of small‐ and large‐for‐gestational‐age ( SGA and LGA ) infants. Furthermore, the clinical potential of the best‐performing models was evaluated. Design Multicentre prospective cohort. Setting Thirty‐six midwifery practices and six hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Systematic reviews have revealed that the vast majority of studies aimed at validating prediction models externally were not conducted well and did not report important elements 23,24 . In general, few studies have examined the external validity of SGA models, showing poor reproducibility for first-trimester algorithms 25 . The new FMF approach for SGA has undergone extensive internal validation [12][13][14][15][16][17][18] , but to date it has not been validated in populations other than the ones used for its development.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have revealed that the vast majority of studies aimed at validating prediction models externally were not conducted well and did not report important elements 23,24 . In general, few studies have examined the external validity of SGA models, showing poor reproducibility for first-trimester algorithms 25 . The new FMF approach for SGA has undergone extensive internal validation [12][13][14][15][16][17][18] , but to date it has not been validated in populations other than the ones used for its development.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the external validity of prediction models for SGA. Meertens et al 27 . demonstrated poor reproducibility for first‐trimester logistic regression algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the external validity of prediction models for SGA. Meertens et al 27 demonstrated poor reproducibility for first-trimester logistic regression algorithms. Comparison of logistic regression models with the competing-risks approach for the prediction of SGA in the context of an internal validation process showed that the latter has superior performance and is more reproducible for predicting preterm SGA 14,15,28 .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…In light of these results, further research should elucidate the reasons for the failed antenatal detection of infants that are SGA, in order to identify preventable factors, such as through audits. Other approaches are to base screening strategies on a broader set of risk markers, 58 using more information about maternal characteristics (age, parity, height and weight, conception method, smoking, medical and obstetrical history, for instance) and integrating biomarkers and biophysical tests (such as glucose, Rhesus group, EFW, vascular flow indices and placental factors) in prediction models 59–61 . However, existing predictive models have modest performance and a net benefit for predicting SGA births compared with current strategies, leading to calls to change the focus from predicting SGA to predicting adverse outcomes associated with suboptimal fetal growth 59 …”
Section: Discussionmentioning
confidence: 99%